Mindfulness-Based Interventions for Parents of Children with Neurodevelopmental Disorders: A Systematic Literature Review - Tiara Minnatul Maula; Sri Redatin Retno Pudjiati (Journal of Educational, Health and Community Psychology, 2026)
Parenting children with Neurodevelopmental Disorders (NDD) involves chronic stressors impacting family well-being. While Mindfulness-Based Interventions (MBIs) reduce stress, recent digital and brief modalities require systematic evaluation. This study synthesizes evidence on MBI effectiveness for parents of children with NDD regarding psychological functioning and parenting outcomes. Following PRISMA 2020 guidelines, a systematic search across seven databases identified 23 eligible studies published between 2016 and 2025. Findings suggest promising benefits of MBIs in reducing parenting stress, anxiety, and depression via de-centering mechanisms, although results are not fully uniform across studies. Crucially, brief and online interventions showed potential efficacy comparable to traditional face-to-face protocols, addressing accessibility barriers. MBIs represent a robust, transdiagnostic intervention for NDD caregivers. The proven efficacy of accessible digital formats suggests a critical avenue for democratizing mental health support for this vulnerable population.